Reducing length of stay for patients presenting to general surgery with acute non‐surgical abdominal pain. Issue 11 (28th August 2020) - de Burlet, Kirsten J.; Desmond, Brendan; Matsis, Raphael; Harper, Simon J.; Larsen, Peter D.; Dennett, Elizabeth R.
Abstract : (a) Computed tomography scans for patients with a non‐surgical diagnosis. (b) Patients with a non‐surgical diagnosis discharged <12 h. Abstract: Background: Acute abdominal pain is a common surgical presentation. We previously found that over the last decade, more patients were admitted to hospital with non‐surgical diagnoses (e.g. gastroenteritis, constipation and non‐specific abdominal pain) and length of stay and use of imaging (mainly computed tomography scan) for these patients increased. This study aimed to reduce length of stay and use of imaging for patients admitted with non‐surgical abdominal pain. Methods: A prospective study was undertaken in a tertiary centre evaluating length of stay and use of additional imaging in patients with a non‐surgical diagnosis after a quality improvement intervention was implemented. Results: A total of 454 patients were included; 204 (44.9%) presented with non‐surgical abdominal pain. During the study period, a significant reduction in computed tomography scan requests was observed (38.5–25.0%, P = 0.037) and an increasing proportion of these patients were discharged within 12 h (33.3–57.1%, P = 0.018). The number of re‐presentations remained unchanged ( P = 0.358). Conclusions: The study intervention increased the proportion of patients with non‐surgical diagnoses that were successfully discharged within 12 h and reduced the use of additional imaging in this group. This may lead to improved use of health care resources for patients with more urgent diagnoses.